KAJIAN PERBAIKAN STRUKTUR PERKERASAN KAKU MENGGUNAKAN METODE PRESSURE GROUTING DENGAN MATERIAL POLYURETHANE DAN EPOXY (Studi Kasus : Ruas Jalan Patriot – Perintis Kemerdekaan Kota Pekalongan) - Junianto, Arif; Ramadhan, Rifqi Maulana; Utari, Jantayu Padma; Kusdiyono, Kusdiyono; Pawiro, Dadiyono Amat; Junaidi, Junaidi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2019)
Today the implementation of road infrastructure development using concrete pavement is experiencing rapid development because it can serve heavy and heavy traffic loads. But there are some problems that often arise in the use of concrete for pavement, causing damage (cracks). Repair of concrete cracks using pressure grouting method is one solution that can be used to improve the strength of concrete. This study discusses the comparison of the effectiveness of using polyurethane and epoxy materials in an effort to improve the rigid pavement structure. The research method used was to carry out repairs to the concrete structure on the Independence Patriotic-Road Section of Pekalongan City using polyurethane and epoxy materials. In this study each of the 5 existing normal (non-damaged) concrete samples, concrete repaired with polyurethane material and repaired concrete using epoxy material using core drill method, which will then be tested for compressive strength in the laboratory, as well as hammer test testing. to find out the strength of the existing concrete damage. The results showed that the average compressive strength of normal existing concrete (not damaged) amounted to 59.20 N/mm2, the average compressive strength of concrete that experienced cracks was 27.04 N/mm2, the average compressive strength value of repair concrete using polyurethane material is 31.92 N/mm2 (increasing by 15.17%) and the average compressive strength of concrete repair using epoxy material is 45.22 N/mm2 (increased by 56.53%).